PERAMALAN TINGKAT PRODUKSI KAKAO TAHUN 2021 DI PROVINSI SUMATERA UTARA DENGAN METODE DOUBLE EXPONENTIAL SMOOTHING BROWN - Handayani, Tri; Lubis, Riri Syafitri; Aprilia, Rima (MAp (Mathematics and Applications) Journal, 2021)
Cocoa production in North Sumatera Province from 2007 to 2018 tends to decline. The low cocoa production in North Sumatera Province is below optimal conditions which impact on the economic sector, so forecasting is necessary in order to support the development of the upcoming cocoa industry in North Sumatera Province. The purpose of this study was to determine the amount of cocoa production in 2021 in North Sumatera Province using the double exponential smoothing brown method. With parameter values Â and values Â obtaining the form of the equation for forecasting the level of cocoa production in 2021 in North Sumatera Province using double exponential smoothing brown is . Form the research result, the amount of cocoa production in 2021 in North Sumatera Province obtained tons.